Numerical simulation on giant reed co-firing performance of circulating fluidized bed in thermal power plant to reduce carbon emission - Jiamiao Liu; Pengbo Zhao; Chenglong Yang; Qingwei Wang; Liujun Chang; Shi'en Liu; Chang'an Wang; Defu Che (Biomass and Bioenergy, 2026)

Excavatolide E triggers oxidative stress-associated apoptosis and DNA damage to inhibit bladder cancer cell proliferation - Che-Wei Yang; Chia-Hung Yen; Tsu-Ming Chien; Szu-Yin Yu; Fang-Rong Chang; Jyh-Horng Sheu; Hsueh-Wei Chang (Molecular Biology Reports, 2026)

Electron-percolation-driven electric-field harmonization reprograms Zn nucleation for ultrastable Zn metal anodes - Jia-Sheng Lin; Daniel Chang; Che-Ning Yeh; Yi-Chun Yang; Hsing-Yu Tuan (Chemical Engineering Journal, 2026)

Agricultural management intensity drives niche partitioning of ammonia oxidizers at three contrasting soil sites - Yu Zeng; Che Tan; Chang Yin; Xiaozhong Wang; Hongsheng Gao; Hua Peng; Yongchao Liang (Applied Soil Ecology, 2026)

A DNA pyramid nanoframe based enzymatic platform for multiplex single nucleotide polymorphism genotyping - Chang Feng; Xinran Che; Bowu Wang; Shiyun Yang; Guanyu Cheng; Xuezhu Wang; Zhihui Zhou; Penghui Zhang; Guifang Chen (Chemical Engineering Journal, 2026)

Green manuring outperforms cattle manure in soil carbon sequestration by reshaping dissolved organic matter composition and fungal life strategies - Siwei Shi; Songjuan Gao; Guopeng Zhou; Danna Chang; Rui Liu; Ting Liang; Jiudong Zhang; Zongxian Che; Weidong Cao (Soil and Tillage Research, 2026)

Conserved crop root economics space drives niche partitioning of ammonia oxidizers - Yu Zeng; Che Tan; Zhihui Wen; Jianbo Shen; Chang Yin; Yongchao Liang (Soil Biology and Biochemistry, 2026)

Dynamics simulation on microstructural properties evolution of high-alkali coal slag in reducing conditions: The roles of alkali oxide, alkaline earth oxides, and iron oxide - Guowei Ma; Junyan Gu; Maoyun Luo; Chang’an Wang; Jiamiao Liu; Yonggang Zhao; Lin Zhao; Limin Wang; Wanzhu Wu; Hu Wang; Defu Che (Fuel, 2026)

Modal coupling and vibration-based identification of individual tensions in interlinked parallel stay cables - Wen-Hwa Wu; Chien-Chou Chen; Che-Wei Chang (Engineering Structures, 2026)

Amorphous CO2-philic molecular networks via covalent coupling for high-performance TFC hollow fiber membranes - Meta Mamo Goro; Zelalem Gudeta Abdi; Qing-Yun Chou; Ching-Han Chou; Che-Wei Chang; Tai-Shung Chung (Chemical Engineering Journal, 2026)

Full-scale field tests on energy storage cabinets under thermal runaway and firefighting response - Chih-Chiang Hsieh; Ming-Che Sung; Chi-Min Shu; Chia-Chin Chang (Process Safety and Environmental Protection, 2026)

Numerical Simulation on product generation and NO emission characteristics of iron Powder-Air combustion in a cyclone burner - Mengjie Wu; Yongbo Du; Chang’an Wang; Yujie Hou; Xinyue Gao; Junyan Gu; Wengang Bai; Defu Che (Fuel, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Caffeinated chewing gum improves military performances in special forces soldiers - Yi-Jie Shiu; Che-Hsiu Chen; Hung-Yu Lin; Chia-Cheng Yang; Chi-Wen Yen; Han-Yuan Chang; Hsuan-Ta Chen; Chih-Hui Chiu (European Journal of Applied Physiology, 2026)

Correlation of ground motion parameters based on strong-motion records and GMPE residuals in western China - Xiufeng Tian; Nana Chang; Minglang Che; Xuan Zhang (Geosciences Journal, 2026)

Design and enhancement of bifunctional g-C3N4/Co-UiO-66-NH2 nanocatalyst for photocatalytic degradation in real samples and electrocatalytic energy conversion applications - Yazhini Priya Subbarayalu; Kasimayan Uma; Nagapandiselvi Perumal; Sathiya Balashanmuga Nehru; Mangalaraja Ramalinga Viswanathan; Che-Wei Chang; Lung-Chien Chen; Zong-Liang Tseng (Journal of Water Process Engineering, 2026)

Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

The state of knowledge for engineering with nature: Vegetation as wave buffer - Xifen Chen; Zhan Hu; Tori Tomiczek; Che-Wei Chang; Dan Cox; Maria Maza; Nobuhito Mori; Siddharth Narayan; Sungwon Shin; Tomohiro Suzuki (Coastal Engineering, 2026)

Urinary Fibroblast Growth Factor-23 and Soluble Alpha-Klotho in Cats with Chronic Kidney Disease - Wei-Che Chen; Wei-Li Hsu; Chao-Chin Chang; Pei-Shiue Jason Tsai; Vin-Cent Wu; Ya-Jane Lee (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Exploring the multiple photochemical behaviors of ionizable EDCs in aquatic environments: Kinetics, intermediates, and toxicity evolution - Linke Ge; Shijing Yang; Nannan Cui; Chang-Er Chen; Xiaojia Che; Peng Zhang (Environmental Research, 2026)

Interrelationships among PM2.5/O3 concentrations, polluted weather patterns, and meteorological conditions over Taiwan based on 2006–2024 observations - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Meng-Hsuan Lee; Ja-Huai Lee; Chih-Chung Chang; Wei-Nai Chen; Chian-Yi Liu (Atmospheric Research, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

Doxorubicin-Induced Cardiotoxicity in Breast Cancer: Mechanistic Pathways, Pharmacogenomic Modifiers, and Translational Strategies - Chi-Tong Kuok; Hao-Wei Lee; Chen-Yu Huang; Yu-Che Cheng; Shih-Chang Lin; Jiun-Wen Guo (Cardiovascular Toxicology, 2026)

In vitro evaluation of Limosilactobacillus and Enterococcus isolates for inhibitory activity against porcine reproductive and respiratory syndrome virus - Chin-Che Chang; Hui-Wen Chang; Je-Ruei Liu (Archives of Microbiology, 2026)

Application of biochar-based permeable reactive barriers in environmental remediation: A critical review - Chang Liu; Ruijie Che; Zhongtian Dong; Jing Hua; Ning Xu; Yining Zhu; Fenghe Wang; Shengtian Zhang (Journal of Environmental Management, 2026)

Joint inversion of hydraulic and thermal parameter fields using a CNN-based framework and transient hydraulic tomography - Che-Wei Liang; Jui-Pin Tsai; Zi-Yan Chou; Chia-Hao Chang; Bo-Tsen Wang (Journal of Hydrology, 2026)

Enhancing water quality and ecological sustainability through intelligent sustainable landscape fountains - Yuan-Hsiou Chang; Hsiao-ling Lu; Tsai-Fu Chuang; Chien-Hsun Chang; Chieh-Hsi Chen; Chien-Che Huang (Ecohydrology & Hydrobiology, 2026)

The enhanced nitrous oxide emissions are driven by prokaryotic ammonia oxidizers and nirK-denitrifiers under various combinations of nitrogen and rice straw in a paddy soil - Chunyan Wu; Yinxiu Liu; Xu Tang; Tao Sun; Che Tan; Yu Zeng; Yan Li; Chang Yin; Yongchao Liang (Soil Ecology Letters, 2026)

The rupture process of the September 2022 Guanshan and Chishang Earthquakes: Joint inversion of seismological and geodetic data - Wei-Yu Zhang; Yu-Sheng Sun; Yopi Serhalawan; Po-Fei Chen; Ming-Che Hsieh; Wu-Lung Chang (Journal of Asian Earth Sciences, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Transition metal-catalyzed oil shale cracking under sub-critical water environments: A kinetic and mechanism study - Chang Che; Zhibing Shen; Hua Song; Ruiyuan Tang; Yang Song; Shibao Yuan; Haiyan Jiang; Haolong Ning; Juntao Zhang; Shengrong Liang (Fuel, 2026)

Association between noise pollution exposure and incident breast cancer in the Sister Study - Brittney A. Gedeon; Che-Jung Chang; Peter James; Rena R. Jones; Alexandra J. White (Environmental Research, 2026)

Noise-resistant automatic seismic framework for monitoring rockslide slope - Chung-Ray Chu; Chiao-Yin Lu; Guan-Wei Lin; En-Jui Lee; Che-Hsin Liu; Chih-Hsin Chang; Hsiao-Yu Huang (Engineering Geology, 2026)

Kinetic insights into the effects of coal quality and operating parameters on the NO and N2O formation behaviors in fluidized bed coal/ammonia co-combustion - Liangxu Dai; Ke Liu; Chang’an Wang; Yujie Hou; Tianlin Yuan; Zixiu Jia; Qiang Lyu; Defu Che (Fuel, 2026)

Experimental study on in-situ pyrolysis of tar-rich coal under CO2 heating: tar-gas products extraction and microstructural evolution - Meijing Chen; Liujun Chang; Chang’an Wang; Tianlin Yuan; Mengjie Wu; Yujie Hou; Defu Che (Fuel, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

Potential role of oocyte-intrinsic fatty acid synthesis in ovarian development of the bigfin reef squid Sepioteuthis lessoniana - Hau-Wen Li; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2026)
In most animals, excess dietary energy is stored as lipids in specialized tissues, such as the liver in vertebrates or the hepatopancreas and fat body in invertebrates, which function as energy reservoirs for reproduction. In cephalopods, however, dietary energy is rapidly mobilized from the digestive gland for growth rather than stored for reproduction. How excess energy is allocated for reproduction activity in cephalopods remains largely unclear. Lipogenesis is initiated by acetyl-CoA carboxylase (ACC), which converts acetyl-CoA derived from dietary carbon sources into malonyl-CoA; subsequent synthesis of saturated fatty acids is catalyzed by fatty acid synthase (FAS). Using the bigfin reef squid as a model, we investigate the role of fas in female development. fas mRNA was highly expressed in ovaries but weak in other tissues, including the lipid-rich digestive gland. fas showed female-biased expression in gonads, with level highest in juvenile ovaries and progressively decreasing to their lowest in mature ovaries. Expression was also high in primary and multiple follicular oocytes but declined in later stages. In situ hybridization and immunohistochemistry confirmed fas mRNA and protein localization in oocytes, particularly in primary and multiple follicular oocytes. In vitro ovarian culture further showed that inhibiting FAS activity enhanced somatic cell proliferation. Together, these findings suggest that squid ovary is a primary site of fatty acid synthesis, supporting early oocyte growth and membrane biogenesis in the absence of dedicated lipid storage tissues. The decline of FAS activity during oogenesis, and the associated reproduction in fatty acid synthesis, may act as a regulatory signal to promote somatic cell proliferation.

Lanthanum strengthens Solanum nigrum remediation of arsenic-contaminated soils: From detoxification mechanisms to risk reduction - Yining Zhu; Ruijie Che; Jing Hua; Chang Liu; Zhongtian Dong; Ning Xu; Mingzhu Xia; Fenghe Wang (Journal of Hazardous Materials, 2026)

Thermodynamic and economic analysis of aluminum-water reaction systems for power generation and energy storage - Xinyue Gao; Yongbo Du; Chang'an Wang; Yujie Hou; Mengjie Wu; Junyan Gu; Wengang Bai; Defu Che (Journal of Cleaner Production, 2026)

NO heterogeneous reduction during oxy-fuel combustion of semi-coke: The role of high-temperature rapid gasification - Pengqian Wang; Chenxi Zhang; Xingpeng Li; Jiaojiao Zhang; Yi Liu; Yongbo Du; Chang’an Wang; Defu Che; Bo Bai (Fuel, 2026)

Proteomic profiling of Monascus-fermented djulis (Chenopodium formosanum) identifies ACE-inhibitory peptides through integrated in silico and in vitro approaches - Jheng-Jhe Lu; Kuan-Chen Cheng; Darin Khumsupan; Chen-Che Hsieh; Chang-Wei Hsieh; Shella Permatasari Santoso; Artik Elisa Angkawijaya; Hsing-Chun Kuo (Food Chemistry, 2026)

Boosting catalytic activity toward industrial water electrolysis: Ag–triggered dual–site activation in NiFe LDH for ultra–efficient oxygen evolution reaction - Habib Gemechu Edao; Chia-Yu Chang; Woldesenbet Bafe Dilebo; Chemeda Barasa Guta; Keseven Lakshmanan; Endalkachew Asefa Moges; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Chun-Chi Chang; Wei-Sheng Liao; Meng-Che Tsai; Wei-Nien Su; et al. (Chemical Engineering Journal, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Assessment of subsystem interactions and coupling coordination in flood resilience evaluation: Comparative analysis and policy recommendations - Yuan-Shun Chang; Kun-Ju Wu; Hao-Che Ho (Urban Climate, 2025)

Long-term substitution of chemical fertilizer with organic manure enhances the activity and autotrophic growth of ammonia-oxidizing archaea and comammox nitrospira in paddy soil - Chunyan Wu; Xu Tang; Che Tan; Tao Sun; Yu Zeng; Yinxiu Liu; Yingxia Liu; Yan Li; Yongchao Liang; Chang Yin (Journal of Environmental Management, 2025)

Design and characterisation of the out-of-plane dielectric elastomer generator for wave energy harvesting - Xi Wang; Jinxin Wang; Tianyou Zhang; Jung-Che Chang; Siqian Li; Yao Zhang; Tianyi Zeng; Xin Dong (Ocean Engineering, 2025)

Simulation study on mineral transformation behaviors and ash fusion characteristics during high-alkali coal combustion under deep peaking conditions - Jiamiao Liu; Guowei Ma; Yongbo Du; Chang’an Wang; Yonggang Zhao; Wanzhu Wu; Longping Shi; Lin Zhao; Defu Che (Fuel, 2025)

Decisive electrocatalyst of oxyphilic transition metals with bivalent metal perovskites: Localized oxygen confinement for enhanced 2e-WOR in H₂O₂ production - Chemeda Barasa Guta; Chia-Yu Chang; Fikiru Temesgen Angerasa; Baru Debtera Bejena; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Endalkachew Asefa Moges; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2025)

Sodium silicate complex reduces subdermal hemorrhage and prolongs survival after envenomation by Trimeresurus stejnegeri stejnegeri - Yen-Chia Chen; Hao-Ming Chang; Chang-Chih Ke; Chia-Chun Liu; Yu-Kai Huang; Kun-Che Chang; Min-Hui Chen; Isaac Chun-Jen Chen; Yu-Wei Chiang; Po-Yu Liu; Chih-Sheng Lai; Kuo-Lung Lai; et al. (Toxicon, 2025)

Chemical structure and bioactivities of a sulfated polysaccharide from precious medicinal fungi - Mei-Kuang Lu; Chi-Hsein Chao; Tsu-Yuan Chang; Ming-Che Cheng; Yu-Chi Hsu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Graft-modified amphiphilic dendron/polyimide regular through-pore composite membranes for oil/water separation - Chien-Chieh Hu; Cai-Syuan Sung; Ru-Jong Jeng; Chien-Hsin Wu; Ying-Chi Huang; Huai-Che Chang; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

Theoretical calculations to identify and design transition metal-based additives for hydrogen storage materials - Thi Thu Le; Jiangming Cao; Svetlana Korneychuk; Wei-che Chang; Marcus Willi Rackel; Denis Kramer; Jürgen Markmann; Fahim Karimi; Astrid Pundt; Thomas Klassen; Claudio Pistidda (Chemical Engineering Journal, 2025)

Atmospheric emerging pollutants of cyclic volatile methyl siloxanes across the Yangtze River Delta region revealed by mobile measurements - Lin Cheng; Yunhua Chang; Haifeng Yu; Xiang Che; Wen Tan; Liang Zhu (Chemosphere, 2025)

Feasibility and limitations of using specific nitrification inhibitors to differentiate ammonia oxidizer activity - Che Tan; Yu Zeng; Cécile Gubry-Rangin; Chang Yin; Yongchao Liang (Soil Biology and Biochemistry, 2025)

Influence of Oxygen-Containing functional groups in sulfonated biochar on 5-Hydroxymethylfurfural synthesis in aqueous Solvents: Mechanistic insights and theoretical analysis - Xuege He; Jiayu Shi; Chang Gao; Wenrong Che; Xianhai Zeng; Miao Zuo (Fuel, 2025)

Effects of using deep learning to predict the geographic origin of barley genebank accessions on genome–environment association studies - Che-Wei Chang; Karl Schmid (Theoretical and Applied Genetics, 2025)
Genome–environment association (GEA) is an approach for identifying adaptive loci by combining genetic variation with environmental parameters, offering potential for improving crop resilience. However, its application to genebank accessions is limited by missing geographic origin data. To address this limitation, we explored the use of neural networks to predict the geographic origins of barley accessions and integrate imputed environmental data into GEA. Neural networks demonstrated high accuracy in cross-validation but occasionally produced ecologically implausible predictions as models solely considered geographical proximity. For example, some predicted origins were located within non-arable regions, such as the Mediterranean Sea. Using barley flowering time genes as benchmarks, GEA integrating imputed environmental data ( $$N=11,032$$ N = 11 , 032 ) displayed partially concordant yet complementary detection of genomic regions near flowering time genes compared to regular GEA ( $$N=1,626$$ N = 1 , 626 ), highlighting the potential of GEA with imputed data to complement regular GEA in uncovering novel adaptive loci. Also, contrary to our initial hypothesis anticipating a significant improvement in GEA performance by increasing sample size, our simulations yield unexpected insights. Our study suggests potential limitations in the sensitivity of GEA approaches to the considerable expansion in sample size achieved through predicting missing geographical data. Overall, our study provides insights into leveraging incomplete geographical origin data by integrating deep learning with GEA. Our findings indicate the need for further development of GEA approaches to optimize the use of imputed environmental data, such as incorporating regional GEA patterns instead of solely focusing on global associations between allele frequencies and environmental gradients across large-scale landscapes.

Enhanced complexity of interkingdom co-occurrence networks in blueberry rhizosphere microbial communities under soil pH stress - Jilu Che; Yaqiong Wu; Hao Yang; Ying Chang; Wenlong Wu; Lianfei Lyu; Xiaomin Wang; Fuliang Cao; Weilin Li (Applied Soil Ecology, 2025)

Simulating the fate and transport of ZnO nanoparticles in a Tidal River: Coupling a form-specific material flow analysis model to a hydrodynamic fate model - Edward Suhendra; Yuanfang Zheng; Yi-Chin Hsieh; Bernd Nowack; Chih-Hua Chang; Wen-Che Hou (NanoImpact, 2025)

Cyclodextrin-based liquid crystals: A novel approach to promote the formation of thermotropic cubic mesophases and their potential applications as electrolytes - Austin Che; Carson O. Zellmann-Parrotta; Diganta Sarkar; Jayar Espejo; Vladimir K. Michaelis; Todd C. Sutherland; Vance E. Williams; Chang-Chun Ling (Carbohydrate Polymers, 2025)

Study on NO formation and ash characteristics during co-combustion of semi-coke and biomass under O2/CO2 conditions - Jinping Zhang; Jingchun Shen; Junyi Fang; Lei Chen; Chang’an Wang; Defu Che (Fuel, 2025)

Field experiment study to assess critical wave conditions leading to failure of mangrove Rhizophora stylosa - Nobuhito Mori; Che-Wei Chang; Kenji Ono; Hironori Noguchi; Shigeyuki Baba; Hideaki Yanagisawa; Toyohiko Miyagi; Naoki Tsuruta; Kojiro Suzuki; Shiro Yamagata; Yusuke Hasegawa; Yu-Lin Tsai; et al. (Coastal Engineering, 2025)

Using unmanned aerial vehicle monitoring for the landslide and dammed lake: a case study of the Xiuluan area in Taiwan - Che-Hsin Liu; Jui-Yi Ho; Horn-Ru Liao; Shih-Chiang Lee; Naoki Sakai; Chen-Yu Chen; Chih-Hsin Chang (Bulletin of Engineering Geology and the Environment, 2025)

Associations between pesticides in honeybees/hive products and adjacent land use in a rural region of Taiwan - Chien-Che Hung; Chung-Wen Hsueh; Wei-Cheng Chang; Lih-Ming Yiin (Science of The Total Environment, 2025)

Study on characterization of tri-phase products and microstructure evolution during in-situ pyrolysis of tar-rich coal at different temperatures - Meijing Chen; Yongbo Du; Chang’an Wang; Tianlin Yuan; Yujie Hou; Liujun Chang; Lei Deng; Defu Che (Fuel, 2025)

High content heteroatoms doped and valuable biomass derived activated carbon composited with graphene for high performance supercapacitors - Ming-Che Cheng; Yu-Sung Chang; Du-Cheng Tsai; Yen-Lin Huang; Fuh-Sheng Shieu (Fuel, 2025)

Fault materials and creep characteristics in mudstone areas: A case study of Chegualin Fault in southwestern Taiwan - Pin-Hao Chen; Yen-Hua Chen; Ming-Chih Hsieh; Yan-Wei Huang; Chien-Che Huang; Wei-Teh Jiang; Jey-Jau Lee; Yao-Chang Lee; Hwo-Shuenn Sheu (Engineering Geology, 2025)

Simulation investigation on separation characteristics of gas-liquid model products from in-situ pyrolysis of tar-rich coal - Tianlin Yuan; Chang’an Wang; Meijing Chen; Fu Yang; Yujie Hou; Li Ma; Zhonghui Duan; Defu Che (Journal of Environmental Chemical Engineering, 2025)

Effects of residual carbon on slag flow characteristics of Zhundong high-alkali coal under oxy-fuel condition - Yuanmao Chen; Chang’an Wang; Maoyun Luo; Lin Zhao; Pengbo Zhao; Defu Che (Fuel, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Release characteristics of arsenic from sediments and its source or sink competition with phosphorus: A case of a great lake with grass-algae alternation - Shuhang Wang; Yongsheng Chang; Wei Huang; Dianhai Yang; Feifei Che (Journal of Environmental Sciences, 2025)

Experimental investigation on thermal conductivity of tar-rich coal under the simulated in-situ conditions - Xing Ning; Xiaole Huang; Xiangyu Xue; Chang’an Wang; Lei Deng; Defu Che (Fuel, 2025)

Comprehensive validation of a compact laser speckle contrast imaging system for vascular function assessment: from the laboratory to the clinic - Meng-Che Hsieh; Chia-Yu Chang; Ching-Han Hsu; Congo Tak Shing Ching; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Seasonality and extreme flooding can override the effects of debris dam removal on riverine species: a case study of macroinvertebrates - Tsung-Tse Hsieh; Jia-Yi Li; Che-Chang Lin; Mei-Hwa Kuo; Ming-Chih Chiu (Aquatic Ecology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Simulation study on seasonal recovery of waste heat and water resources in flue gas and slurry after WFGD - Gaofeng Fan; Xinyue Gao; Chang’an Wang; Yujie Hou; Jinming Zhang; Jie Xu; Defu Che (Process Safety and Environmental Protection, 2025)

Experimental investigation on gas-liquid–solid tri-phase product distributions during the simulated in-situ pyrolysis of tar-rich coal - Meijing Chen; Chang’an Wang; Tianlin Yuan; Xing Ning; Xiaole Huang; Lei Deng; Defu Che (Fuel, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

Eco-friendly lamellar structured graphene oxide-Lysine nanocomposite membranes with varying d-spacing for enhanced pervaporation desalination - Shalligito Habetamu Abebe; Hannah Faye M. Austria; T.M. Subrahmanya; Huai-Che Chang; Tsung-Han Huang; Gabriel V. Carballo; Wei-Song Hung; Chien-Chieh Hu; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

SPH simulations to investigate the influence of realistic mangroves in reducing breaking wave forces on coastal structures - Shengzhe Wang; Che-Wei Chang (Ocean Engineering, 2025)

Experimental study on characteristics and mechanism of hydrogen production from aluminium–water reaction for carbon-free power generation - Xinyue Gao; Chang’an Wang; Yujie Hou; Lin Zhao; Wengang Bai; Defu Che (Fuel, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Environmental acidification drives inter-organ energy mobilization to enhance reproductive performance in medaka (Oryzias latipes) - Hsin-Ju Chuang; Ling Chiu; Bo-Jun Liao; Chun-Yung Chang; Guan-Chung Wu; Yung-Che Tseng; Ming-Yi Chou; Pung-Pung Hwang (Journal of Hazardous Materials, 2024)

Experimental study and chemical equilibrium calculation on the mineral transformation of high-alkali coal under oxy-fuel condition - Lin Zhao; Chang’an Wang; Yingchao Nie; Yongxu Chen; Jinming Zhang; Maoyun Luo; Defu Che (Fuel, 2024)

Efficient PDS activation and carrier extraction by Gd2O3 decorated SrTiO3 for Fenton-like photocatalysis - Bo Feng; Kaining Sun; Guangbo Che; Tianyi Yang; Yongya Zhang; Qianqian He; Tianrui Chang; Lijing Wang; Renquan Guan (Chemical Engineering Journal, 2024)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

Vitamin C alleviates hyperglycemic stress in retinal pigment epithelial cells - Hamid Alahmari; Chia-Chun Liu; Elizabeth Rubin; Venice Y. Lin; Paul Rodriguez; Kun-Che Chang (Molecular Biology Reports, 2024)

Chemical kinetics simulation on nitrogen migration characteristics during co-combustion of ammonia and coal under deeply fuel-air multistage conditions - Liangxu Dai; Chang’an Wang; Yujie Hou; Guowei Ma; Yongxu Chen; Abu Hurera; Lei Zhou; Defu Che (Fuel, 2024)

Novel electrocatalyst with abundant oxygen vacancies enabling efficient two-electron water oxidation reaction for H2O2 synthesis - Chemeda Barasa Guta; Habib Gemechu Edao; Woldesenbet Bafe Dilebo; Chia-Yu Chang; Fikiru Temesgen Angerasa; Endalkachew Asefa Moges; Yosef Nikodimos; Keseven Lakshmanan; Meng-Che Tsai; Wei-Nien Su; Bing Joe Hwang (Chemical Engineering Journal, 2024)

Metabolites of blueberry roots at different developmental stages strongly shape microbial community structure and intra-kingdom interactions at the root-soil interface - Jilu Che; Yaqiong Wu; Hao Yang; Ying Chang; Wenlong Wu; Lianfei Lyu; Xiaomin Wang; Fuliang Cao; Weilin Li (Science of The Total Environment, 2024)

Residential proximity to toxic metal-emitting industrial sites and toenail metal concentrations in a United States-wide prospective cohort - Meklit Daniel; Jennifer L. Ish; Jessica M. Madrigal; Che-Jung Chang; Kaitlyn G. Lawrence; Jared A. Fisher; Keith E. Levine; Brittany A. Trottier; Rena R. Jones; Dale P. Sandler; Alexandra J. White (Environmental Research, 2024)

The role of ALDH1A1 in glioblastoma proliferation and invasion - Yu-Kai Huang; Tzu-Ming Wang; Chi-Yu Chen; Chia-Yang Li; Shu-Chi Wang; Khushboo Irshad; Yuan Pan; Kun-Che Chang (Chemico-Biological Interactions, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Coseismic and subsequent landslides of the 2024 Hualien earthquake (M7.2) on April 3 in Taiwan - Jui-Ming Chang; Wei-An Chao; Che-Ming Yang; Ming-Wan Huang (Landslides, 2024)

Long-term green manuring increases soil carbon sequestration via decreasing qCO2 caused by lower microbial phosphorus limitation in a dry land field - Zhengbo Ma; Ting Liang; Haoran Fu; Qingxu Ma; Danna Chang; Jiudong Zhang; Zongxian Che; Guopeng Zhou; Weidong Cao (Agriculture, Ecosystems & Environment, 2024)

Research progress of natural polysaccharide-based and natural protein-based hydrogels for bacteria-infected wound healing - Huiqing Xu; Yilin Che; Rui Zhou; Lu Wang; Jiaying Huang; Wei Kong; Chang Liu; Lei Guo; Yixin Tang; Xue Wang; Xi Yang; Erlei Wang; et al. (Chemical Engineering Journal, 2024)

Insecticide resistance and characteristics of mutations related to target site insensitivity of diamondback moths in Taiwan - Chia-Che Chang; Shu-Mei Dai; Chien-Yu Chen; Li-Hsin Huang; Yu-Hsien Chen; Ju-Chun Hsu (Pesticide Biochemistry and Physiology, 2024)

Identification of synthetic cathinone positional isomers using electron activated dissociation mass spectrometry - Peng Che; Christina Chang; Patrick Buzzini; Lavinia Stegemann; Jeroen Kool; J. Tyler Davidson; Isabelle Kohler (Analytica Chimica Acta, 2024)

Exploring the biphasic dose-response effects of photobiomodulation on the viability, migration, and extracellular vesicle secretion of human adipose mesenchymal stem cells - Che-Yi Chang; Ana Elena Aviña; Cheng-Jen Chang; Long-Sheng Lu; Yi-Yong Chong; Tzu Ying Ho; Tzu-Sen Yang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Deciphering the functional importance of comammox vs. canonical ammonia oxidisers in nitrification and N2O emissions in acidic agricultural soils - Che Tan; Chang Yin; Lei Zhang; Yu Zeng; Cécile Gubry-Rangin; Hao Chen; Zixiang Gao; Hongyun Peng; Tingqiang Li; Yongchao Liang (Soil Biology and Biochemistry, 2024)

Enhancing flood verification using Signal Detection Theory (SDT) and IoT Sensors: A spatial scale evaluation - Che-Hao Chang; Riki Rahmad; Shiang-Jen Wu; Chih-Tsung Hsu; Po-Hsien Chung (Journal of Hydrology, 2024)

Effects of SO2 and H2O on the ash deposition and NO emission during oxy-fuel combustion of high-alkali coal - Lin Zhao; Chang’an Wang; Tianlin Yuan; Liangxu Dai; Yingchao Nie; Guowei Ma; Lei Zhou; Maoyun Luo; Defu Che (Process Safety and Environmental Protection, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Excavatolide C/cisplatin combination induces antiproliferation and drives apoptosis and DNA damage in bladder cancer cells - Tsu-Ming Chien; Che-Wei Yang; Chia-Hung Yen; Bi-Wen Yeh; Wen-Jeng Wu; Jyh-Horng Sheu; Hsueh-Wei Chang (Archives of Toxicology, 2024)

Traction-based implementation of transmitting boundaries for nonlinear seismic Soil–Structure interaction analyses - Che-Yu Chang; Wen-Chia Yang; Chen-Hsiang Kuo (Soil Dynamics and Earthquake Engineering, 2024)

New insight into oxygen vacancy and synergism in CuCeOx catalysts based on the toluene oxidation - Guangtao Hu; Zirui Zhang; Chang’an Wang; Guojie Li; Dandan Zhou; Jinshi Wang; Defu Che; Running Kang (Journal of Environmental Chemical Engineering, 2024)

Novel Multiplexed High Throughput Screening of Selective Inhibitors for Drug-Metabolizing Enzymes Using Human Hepatocytes - Jianhua Liu; Daria Vernikovskaya; Gary Bora; Anthony Carlo; Woodrow Burchett; Samantha Jordan; Lloyd Wei Tat Tang; Joy Yang; Ye Che; George Chang; Matthew D. Troutman; Li Di (The AAPS Journal, 2024)

Characterization of phosphate solubilizing bacteria in the sediments of eutrophic lakes and their potential for cyanobacterial recruitment - Chengqi Tu; Xiaoshuang Dong; Haoran Yang; Yongsheng Chang; Zhongshuo Xu; Feifei Che; Shuhang Wang; Wei Huang (Chemosphere, 2024)

Driving effects of dissolved organic carbon on cadmium release of the sediments by cyanobacterial decomposition - Shuhang Wang; Yongsheng Chang; Dianhai Yang; Wei Huang; Feifei Che (Journal of Water Process Engineering, 2024)

Green manuring relocates microbiomes in driving the soil functionality of nitrogen cycling to obtain preferable grain yields in thirty years - Guopeng Zhou; Kunkun Fan; Songjuan Gao; Danna Chang; Guilong Li; Ting Liang; Hai Liang; Shun Li; Jiudong Zhang; Zongxian Che; Weidong Cao (Science China Life Sciences, 2024)

Occurrence characteristics and risk assessment of microplastics in agricultural soils in the loess hilly gully area of Yan' an, China - Zhifeng Jia; Wei Wei; Yanhua Wang; Yingjie Chang; Rui Lei; Yanhong Che (Science of The Total Environment, 2024)

Aldose reductase is a potential therapeutic target for neurodegeneration - Mishal Rao; Kun-Che Chang (Chemico-Biological Interactions, 2024)

Response mechanism of sediment endogenous phosphorus release to functional microorganisms and its cyanobacterial growth and disappearance effects - Wei Huang; Xiaoshuang Dong; Chengqi Tu; Haoran Yang; Yongsheng Chang; Xixi Yang; Haojie Chen; Feifei Che (Science of The Total Environment, 2024)

Bioaccumulation of PFASs in cabbage collected near a landfill site in China: Laboratory and field investigations - Jilu Che; Chang Xu; Xin Song; Xiaoyan Ding; Mukhtiar Ali; Hong Chen (Science of The Total Environment, 2024)

The coupled effect of sediment resuspension and microbiota on phosphorus release and transformation in a simulated aquatic ecosystem - Haoran Yang; Yongsheng Chang; Xiaoshuang Dong; Shuhang Wang; Feifei Che; Wei Huang (Journal of Water Process Engineering, 2024)

Structure-specific metabolism of flavonol molecules by Bacillus subtilis var. natto BCRC 80517 - Che-Wei Wang; Hsin-Ya Tsai; Chen Hsu; Ching-Chun Hsieh; I-Shu Wang; Chi-Fon Chang; Nan-Wei Su (Food Chemistry, 2024)

Revisit the classical Newmark displacement analysis for earthquake-induced wedge sliding of a rock slope - Che-Ming Yang; Jia-Jyun Dong; Chyi-Tyi Lee; Hui-Yun Cheng; Chang-Hsuan Hsu; Thi-Phuong Nguyen; Chun-Jung Lai; Wen-Jie Wu (Engineering Geology, 2024)

Exposure to phenols reduces melanogenesis in B16F10 cells and zebrafish - Chung-Yu Lin; Chang-Yi Wu; Chia C. Wang; Che-Hsin Lee (Aquatic Toxicology, 2024)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

Spatiotemporal variations and influential factors affecting reproductive dynamics of Pacific saury in the Northwest Pacific during fishing season - Wei‐Che Hung; Jhen Hsu; Yi‐Jay Chang; Wen‐Bin Huang; Chih‐Hao Hsieh; Ming‐Tsung Chung (Journal of Fish Biology, 2023)
This study examined the spatial and monthly variations in reproductive dynamics of Pacific saury collected in the high sea (40°N−49°N, 149°E−168°E) of the northwestern Pacific during the fishing season of the Taiwanese stick‐held dip‐net fisheries (July–November) from 2018 to 2019. Generalized additive mixed‐effects models (GAMMs) were applied to explore the relationship between the probability of maturing and spawning occurrence ( P MOS ) and the explanatory variables (month, body length, sea‐surface temperature [SST] as fixed effects, and fishing set as a random effect) for the age 0 and age 1 fish, respectively. In addition, the impact of the geographical difference in growth rates of age 0 fish, quantified as the radius of the otolith annual ring, on the P MOS of age 1 fish was explored in the GAMMs. Results showed that the mean values of the condition factor (CF) varied by months, and higher mean CFs were observed north of 45°N. However, the mean values of the gonado‐somatic index did not show a clear spatiotemporal pattern. The spatial distribution of the ovarian maturation states revealed that the spawning ground of Pacific saury during July–November was broader than that previously known and had partly overlapped with the high‐sea fishing ground. The best GAMM showed that the predicted P MOS of the age 0 fish were generally low (mean = 19%, standard deviation [SD] = 10%) and tended to increase with increasing body length. In contrast, the predicted P MOS were relatively higher (mean = 37%, SD = 10%) for the age 1 fish and increased with increasing SST and decreasing latitude. Two candidate GAMMs, which are equally supported as the best model (ΔAIC

The microbial mechanisms by which long-term heavy metal contamination affects soil organic carbon levels - Zhineng Xiao; Changqun Duan; Shiyu Li; Ji Chen; Changhui Peng; Rongxiao Che; Chang'e Liu; Yin Huang; Runran Mei; Liangliang Xu; Pengfei Luo; Yadong Yu (Chemosphere, 2023)

Designing, analyzing, and experimentally verifying a uniaxial shear box for investigating the length effect of buried pipelines during soil liquefaction - Hsuan-Chih Yang; Che-Yu Chang; Kuan-Yu Chen; Hsin-Chen Chou (Transportation Geotechnics, 2023)

Analysis and classification of coffee beans using single coffee bean mass spectrometry with machine learning strategy - Jia-Jen Tsai; Che-Chia Chang; De-Yi Huang; Te-Sheng Lin; Yu-Chie Chen (Food Chemistry, 2023)

The important role of fluid chemistry in the hydrothermal alteration of ordinary chondrites: Insights from halite and sphalerite in the Sidi El Habib 001 (H5) meteorite - Shaofan Che; Kenneth J. Domanik; Yao-Jen Chang; Thomas J. Zega (Earth and Planetary Science Letters, 2023)

Ultrafine particles in urban settings: A combined study of volatility and effective density revealed by VT-DMA-APM - Che-An Wu; Yu-Ting Chen; Li-Hao Young; Po-Kai Chang; Li-Ti Chou; Albert Y. Chen; Ta-Chih Hsiao (Atmospheric Environment, 2023)

An efficiency-driven approach for global ecological industrial parks - Shih-Fang Lo; Wen-Min Lu; Che-Wei Chang; Shiu-Wan Hung; Li-Ling Yang (Journal of Cleaner Production, 2023)

Synchronous regulation of Schottky/p-n dual junction in Prussian blue-derived Janus heterostructures: A path to ultrafast long life potassium ion batteries - Shou-Shan Mai; Kai-Yuan Hsiao; Yi-Chun Yang; Ying-Rui Lu; Ming-Yen Lu; Yi-Yen Hsieh; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

A rebuttal to “Response to “Feremycorrhizal fungi: A confusing and erroneous term”: Feremycorrhiza means ‘nearly mycorrhiza’; hence, it is a clear and correct term because the fungal partner has mycorrhizal traits and lineage” - Christopher P. Chanway; Akshit Puri; Kiran Preet Padda; Che-Wei Chang (Biology and Fertility of Soils, 2023)

Duplicated paralog of sulfide: quinone oxidoreductase contributes to the adaptation to hydrogen sulfide-rich environment in the hydrothermal vent crab, Xenograpsus testudinatus - Chi Chen; Guan-Chung Wu; Yao-Tse Chung; Hau-Wen Li; Pei-Hsuan Chou; Yung-Che Tseng; Chieh-Jhen Chen; Sylvie Dufour; Ching-Fong Chang (Science of The Total Environment, 2023)

Field experiments: How well can seismic monitoring assess rock mass falling? - Jui-Ming Chang; Wei-An Chao; Yu-Ting Kuo; Che-Ming Yang; Hongey Chen; Yu Wang (Engineering Geology, 2023)

Dissolution behavior of ZnO nanoparticles at environmentally relevant low concentrations in surface waters: Equilibrium and kinetics - Yi-Chin Hsieh; Edward Suhendra; Chih-Hua Chang; Wen-Che Hou (Science of The Total Environment, 2023)

High-entropy transition metal disulfide colloid clusters: synergistic atomic scale interaction and interconnected network for ultra-stable potassium ion storage - Yan-Jie Liao; Wei-Wen Shen; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

The effect of maternal consumption of high-fat diet on ovarian development in offspring - Wenyan Wei; Feng Qin; Junjie Gao; Junlei Chang; Xujing Pan; Xuemei Jiang; Lianqiang Che; Yong Zhuo; De Wu; Shengyu Xu (Animal Reproduction Science, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Effect of support condition on the mechanical behavior of ductile iron pipes buried at shallow depth within the backfill of controlled low strength material - Hsuan-Chih Yang; Che-Yu Chang; Gee-Yu Liu; Pao-Ching Chou (Transportation Geotechnics, 2023)

Experimental investigation on co-combustion characteristics of semi-coke and coal: Insight into synergy and blending method - Pengqian Wang; Chang’an Wang; Chaowei Wang; Yongbo Du; Defu Che (Process Safety and Environmental Protection, 2023)

A novel magnetic buoyant-bead flotation method for the removal of typical microalgae from harmful algal blooms - Yan Zhao; Xuexue Wu; Wenjuan Chang; Wenlu Che; Yi Liu; Yanpeng Li (Journal of Environmental Chemical Engineering, 2023)

Production and analysis of metabolites from solid-state fermentation of Chenopodium formosanum (Djulis) sprouts in a bioreactor - Chen-Che Hsieh; Shu-Han Yu; Kai-Wen Cheng; Yu-Wei Liou; Cheng-Chih Hsu; Chang-Wei Hsieh; Chia-Hung Kuo; Kuan-Chen Cheng (Food Research International, 2023)

Long-term maize and pea intercropping improved subsoil carbon storage while reduced greenhouse gas emissions - Lu Yang; Yue Luo; Binglin Lu; Guopeng Zhou; Danna Chang; Songjuan Gao; Jiudong Zhang; Zongxian Che; Weidong Cao (Agriculture, Ecosystems & Environment, 2023)

Simulation study on fuel-nitrogen migration characteristics of oxy-fuel co-combustion of various ultra-low volatile coal-based solid fuels - Chaowei Wang; Chang’an Wang; Maoyun Luo; Liangxu Dai; Pengqian Wang; Defu Che (Process Safety and Environmental Protection, 2023)

Investigation on Co-combustion characteristics and NO emissions of coal and municipal sludge in a tangentially fired boiler - Chang'an Wang; Meijing Chen; Pengbo Zhao; Lei Zhou; Yujie Hou; Jinming Zhang; Qiang Lyu; Defu Che (Fuel, 2023)

Probing air pollution in the Taichung metropolitan area, Taiwan.Part 1: Comprehensive model evaluation and the spatial-temporal evolution of a PM2.5 pollution event - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Wei-Nai Chen; Chian-Yi Liu; Chih-Chung Chang (Atmospheric Research, 2023)

The development of ocean governance for marine environment protection: Current legal system in Taiwan - Yi-Che Shih; Wei Chung Chen; Tai-An Peter Chen; Chih-wei Chang (Frontiers in Marine Science, 2023)
Taiwan establishes Ocean Affairs Council (OAC) in 2018. Ocean governance has reached a new milestone. In 2019, the Ocean Basic Act was enacted. In 2020, the National Ocean Policy White Paper was published, meaning that Taiwan has specialized ocean authorities, regulations, enforcement units, and relevant mechanisms and policies. The Ocean Conservation Administration (OCA) is also responsible for marine environmental protection and conservation. To ensure good ocean governance, maintain marine resources, and protect the environment, the OCA has recently drafted the Marine Conservation Act for sustainable development. This article mainly reviews, analyzes, and compares Taiwan’s current marine-related laws and regulations and refers to the laws, policies, and mechanisms of other countries to provide suggestions on marine governance and the ongoing draft of the Marine Conservation Act.

First report of Rhizoctonia solani AG-4 HG-I causing leaf blight disease on Cattleya × hybrid in Taiwan - Ya-Chu Hsieh; Che-Wei Chang; Chao-Jen Wang (Journal of General Plant Pathology, 2023)

Associations between exposure to brominated flame retardants and metabolic syndrome and its components in U.S. adults - Zhiqiang Che; Huixun Jia; Renjie Chen; Keyu Pan; Zhe Fan; Chang Su; Zhenyu Wu; Tao Zhang (Science of The Total Environment, 2023)

Toxicity prediction: An application of alternative testing and computational toxicology in contaminated groundwater sites in Taiwan - Rachelle D. Arcega; Rong-Jane Chen; Pei-Shan Chih; Yi-Hsuan Huang; Wei-Hsiang Chang; Ting-Khai Kong; Ching-Chang Lee; Trias Mahmudiono; Chun-Chih Tsui; Wen-Che Hou; Hsin-Ta Hsueh; Hsiu-Ling Chen (Journal of Environmental Management, 2023)

Oxygen vacancies endow atomic cobalt-palladium oxide clusters with outstanding oxygen reduction reaction activity - Thomas Yang; Dinesh Bhalothia; Hong-Wei Chang; Che Yan; Amisha Beniwal; You-Xun Chang; Shun-Chi Wu; Po-Chun Chen; Kuan-Wen Wang; Sheng Dai; Tsan-Yao Chen (Chemical Engineering Journal, 2023)

Transcriptomic profile of symbiotic accessory nidamental gland during female maturation in bigfin reef squid - Peng-Wei Tseng; Hau-Wen Li; Chih Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2023)
The bigfin reef squid, Sepioteuthis lessoniana , are a valuable commercial species in East Asian regions such as Taiwan and Japan. A lack of genomic information limits the application of potential aquaculture techniques, especially in breeding when considering the hatching rate of offspring. In some squids and cuttlefishes, symbiotic bacteria are transmitted from the accessory nidamental gland (ANG) to the jelly coat of eggs. In Hawaiian bobtail squid, these parent-delivered mutualistic bacteria play an important role in preventing lethal biofouling of the eggs and accelerating the hatch rate of offspring. The bacterial consortium, which is housed in the female squids ANG, are governed by host selection during female maturation. Immune functions are typically used to explain the regulatory mechanism of symbioses by host selection. In this study, we evaluated the transcripts featured in bacterial selection and maintenance during ANG development using RNA-seq. Different developmental stages of ANGs (stages 1–4) were sequenced. The de novo transcriptome assembly resulted in 524,918 unigenes. Two groups, non-pigmentation group (stage 1 and stage 3) and pigmentation group (stage 4), were clustered by transcriptome-wide expression profile analysis. The gene expression analyses indicated that 9,475 differential expression genes (DEGs) in three different phases and 1,363 (14.3%) DEGs were matched in the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. Furthermore, KEGG-enriched analysis results suggested that immune responses are a dominant pathway in the non-pigmentation group (stage 1 and stage 3) whereas lipid metabolism and metabolism of flora fermentation are dominant in the pigmentation group (stage 4). Although the host immunity plays an important role during bacterial colonization of the ANG in bigfin reef squid, our results showed that most immune-related genes had a reduced transcriptomic level in the pigmentation group compared with the non-pigmentation group. Therefore, our results provide new insight to understand the regulatory mechanisms of initial bacterial colonization and later bacterial pigmentation in the bigfin reef squid.

Numerical simulation on co-firing ultra-low volatile carbon-based fuels with bituminous coal under oxy-fuel condition - Chang'an Wang; Yujie Hou; Qinqin Feng; Chaowei Wang; Xinyue Gao; Defu Che (Fuel, 2023)

Digital elevation models for high-resolution base flood elevation mapping in a densely populated city - Song-Yue Yang; Shaohua Marko Hsu; Ching Hsiao; Che-Hao Chang (Natural Hazards, 2022)

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

circ-Ncam2 (mmu_circ_0006413) Participates in LPS-Induced Microglia Activation and Neuronal Apoptosis via the TLR4/NF-κB Pathway - Kai Guo; Yulin Chang; Yutao Jin; Hong Yuan; Ping Che (Journal of Molecular Neuroscience, 2022)

Outburst debris flow of Yusui Stream caused by a large-scale Silabaku landslide, Southern Taiwan - Che-Ming Yang; Wei-An Chao; Meng-Chia Weng; Yu-Yao Fu; Jui-Ming Chang; Wei-Kai Huang (Landslides, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Using DeepLab v3 + -based semantic segmentation to evaluate platelet activation - Tsung-Chen Kuo; Ting-Wei Cheng; Ching-Kai Lin; Ming-Che Chang; Kuang-Yao Cheng; Yun-Chien Cheng (Medical & Biological Engineering & Computing, 2022)

The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Hau-Wen Li; Wei-Lun Kuo; Chi Chen; Yung-Che Tseng; Ching-Fong Chang; Guan-Chung Wu (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri ( V. fischeri ). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid ( Sepioteuthis lessoniana ) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid ( sl PGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant sl PGRP2 had a negative effect of Escherichia coli ( E.coli ) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.

Variation of uncertainty of drainage density in flood hazard mapping assessment with coupled 1D–2D hydrodynamics model - Song-Yue Yang; Che-Hao Chang; Chih-Tsung Hsu; Shiang-Jen Wu (Natural Hazards, 2022)
Coupled 1D–2D hydrodynamic models are widely utilized in flood hazard mapping. Previous studies adopted conceptual hydrological models or 1D hydrodynamic models to evaluate the impact of drainage density on river flow. However, the drainage density affects not only river flow, but also the flooded area and location. Therefore, this work adopts the 1D–2D model SOBEK to investigate the impact of drainage density on river flow. The uncertainty of drainage density in flood hazard mapping is assessed by a designed case and a real case, Yanshuixi Drainage in Tainan, Taiwan. Analytical results indicate that under the same return period rainfall, reduction in tributary drainages in a model (indicating a lower drainage density) results in an underestimate of the flooded area in tributary drainages. This underestimate causes higher peak discharges and total volume of discharges in the drainages, leading to flooding in certain downstream reaches, thereby overestimating the flooded area. The uncertainty of drainage density decreases with increased rainfall. We suggest that modeling flood hazard mapping with low return period rainfalls requires tributary drainages. For extreme rainfall events, a lower drainage density could be selected, but the drainage density of local key areas should be raised.

Responsiveness to contest experiences is associated with competitive ability but not aggressiveness or boldness - Yu-Ju Chen; Yu-Ting Chang; Yung-Che Tseng; Yuying Hsu (Behavioral Ecology and Sociobiology, 2022)

Life span of a landslide dam on mountain valley caught on seismic signals and its possible early warnings - Che-Ming Yang; Jui-Ming Chang; Chi-Yao Hung; Chih-Heng Lu; Wei-An Chao; Keng-Hao Kang (Landslides, 2022)
Outburst flooding after a landslide dam breach causes global fatalities and devastation. Information on the timing, magnitude, and location of the landslide dam is crucial to hazard assessment. Despite recent efforts, successful real-time detection of landslide dams in mountain valleys and dam breakages is rare. Here, we present a series of seismic analysis including landslide detection, identification of landslide dam formations, and monitoring of dam breaches. We show the working of our analysis on a recent landslide dam that occurred in eastern Taiwan. The results indicate that our seismic analysis provides important information on the location and magnitude of landslides and the dam forming based on data acquired from a regional broadband seismic network. Furthermore, we see that the failure of the landslide dam is directly caught by the riverside seismic signals. To provide warning times for impending floods to downstream areas, we believe that proximal high-quality seismic signals along the river channel are viable options for an operational real-time monitoring system, for landslide dams occurring in mountain valleys. Our work can be a starting point to raise awareness in the community.

Nocturnal Eyes in Slipper Lobsters (Decapoda Scyllaridae): Physiological and Ecological Implications of Habitat Depths for Visual Traits - Oki Hayasaka; Hao-Yi Chang; Li-Chun Li; Yung-Che Tseng; Yi Ta Shao (Frontiers in Marine Science, 2022)
The light characteristics of an ecosystem drive evolutionary adaptations in visual traits, enhancing the diversity and abundance of species living there. The visual systems of crustaceans are highly diverse and often correspond to the optical properties of their preferred environments. Although habitat depth is known to greatly influence visual specialization in marine crustaceans, it remains unclear whether depth drives visual adaptions in nocturnal species. Slipper lobsters (Scyllaridae) are nocturnal benthic marine crustaceans distributed throughout a wide range of depths. In order to understand the visual adaptive capabilities of slipper lobsters inhabiting different depths, we characterized the eye structures of a shallow-water species ( Parribacus japonicas ), an intermediate-depth species ( Scyllarides squammosus ) and a deep-water species ( Ibacus novemdentatus ). Moreover, we measured by electroretinogram (ERG) the spectral sensitivities and temporal resolutions for each species using the following light stimuli: UV (λ max 386 nm), blue (λ max 462 nm), green (λ max 518 nm), yellow (λ max 590 nm), and red (λ max 632 nm). Our histological experiments show that all three species possess a typical superposition compound eye with square facets, and their ERG measurements revealed a single sensitivity peak for each species. Notably, peak spectral sensitivity corresponded to habitat depth, with the estimated peak for I. novemdentatus (493.0 ± 9.8 nm) being similar to that of S. squammosus (517.4 ± 2.1 nm), but lower than that of P. japonicus (537.5 ± 9.9 nm). Additionally, the absolute sensitivities at respective peak wavelengths for I. novemdentatus and P. japonicus were higher than that of S. squammosus . No differences were observed among the three species for maximum critical flicker fusion frequency (CFF max ) across light stimuli. However, P. japonicus had lower CFF max values than the other two species. These data suggest that all three nocturnal slipper lobsters are likely monochromatic and well adapted to dim light environments. Significantly, the deep-water slipper lobster displayed higher spectral sensitivities at shorter wavelengths than the shallow water species, but temporal resolution was not compromised.

On-Site Investigations of Coastal Erosion and Accretion for the Northeast of Taiwan - Ting-Yu Liang; Chih-Hsin Chang; Shih-Chun Hsiao; Wei-Po Huang; Tzu-Yin Chang; Wen-Dar Guo; Che-Hsin Liu; Jui-Yi Ho; Wei-Bo Chen (Journal of Marine Science and Engineering, 2022)
Coastal erosion is a major natural hazard along the northeastern shoreline (i.e., Yilan County) of Taiwan. Analyses of the evolution of the 0 m isobath of the Yilan County coastline indicate that erosion and accretion are occurring north and south of Wushi Fishery Port, respectively, because of jetty and groin construction. Topographic and bathymetric surveys involving the measurement of 43 cross sections were conducted in 2006, 2012, 2013, and 2019. The cross-shore profile comparisons reveal that the erosion of onshore dunes is significant in the northern Jhuan River estuary. Due to the establishment of a nature reserve in the southern Lanyang River estuary, the sediments are carried northward by tidal currents, and accretion is inevitable in the northern Lanyang River estuary. The results of the bathymetric surveys also suggest that the shoreline of Yilan County tends to accrete in summer because of abundant sediment from the rivers; however, it is eroded in winter, owing to the large waves induced by the northeast monsoon. Additionally, the calculated net volume of erosion and accretion between each pair of cross sections shows that the length of coastline impacted by estuarine sediment transport is approximately 2 km long from north to south along the coastline of the Lanyang River estuary.

An innovative targeted therapy for fluoroscopy-induced chronic radiation dermatitis - Kai-Che Wei; Shih-Fan Lai; Wei-Lun Huang; Kuo-Chung Yang; Ping-Chin Lai; Wan-Ju Wei; Tsung-Hsien Chang; Yun-Chen Huang; Ya-Chuan Tsai; Shin-Chih Lin; Sun-Jang Lin; Shih-Chieh Lin (Journal of Molecular Medicine, 2022)
Fluoroscopy-induced chronic radiation dermatitis (FICRD) is a complication of fluoroscopy-guided intervention. Unlike acute radiation dermatitis, FICRD is different as delayed onset and usually appears without preexisting acute dermatitis. Unfortunately, the chronic and progressive pathology of FICRD makes it difficult to treat, and some patients need to receive wide excision and reconstruction surgery. Due to lack of standard treatment, investigating underlying mechanism is needed in order to develop an effective therapy. Herein, the Hippo pathway is specifically identified using an RNA-seq analysis in mild damaged skin specimens of patients with FICRD. Furthermore, specific increase of the Yes-associated protein (YAP1), an effector of the Hippo pathway, in skin region with mild damage plays a protective role for keratinocytes via positively regulating the numerous downstream genes involved in different biological processes. Interestingly, irradiated-keratinocytes inhibit activation of fibroblasts under TGF-β1 treatment via remote control by an exosome containing YAP1. More importantly, targeting one of YAP1 downstream genes, nuclear receptor subfamily 3 group C member 1 (NR3C1), which encodes glucocorticoid receptor, has revealed its therapeutic potential to treat FICRD by inhibiting fibroblasts activation in vitro and preventing formation of radiation ulcers in a mouse model and in patients with FICRD. Taken together, this translational research demonstrates the critical role of YAP1 in FICRD and identification of a feasible, effective therapy for patients with FICRD. Key messages • YAP1 overexpression in skin specimens of radiation dermatitis from FICRD patient. • Radiation-induced YAP1 expression plays protective roles by promoting DNA damage repair and inhibiting fibrosis via remote control of exosomal YAP1. • YAP1 positively regulates NR3C1 which encodes glucocorticoid receptor expression. • Targeting glucocorticoid receptor by prednisolone has therapeutic potential for FICRD patient.

Association between exposure to road traffic noise and hearing impairment: a case-control study - Tang-Chuan Wang; Ta-Yuan Chang; Richard S. Tyler; Bing-Fang Hwang; Yi-Hung Chen; Che-Ming Wu; Chiu-Shong Liu; Kuang-Chao Chen; Chia-Der Lin; Ming-Hsui Tsai (Journal of Environmental Health Science and Engineering, 2021)

Exploring the Deeper Crustal Structure Beneath the Tatun Volcanic Area, Taiwan - Chien-Min Su; Wei-Jhe Wu; Strong Wen; Yi-Heng Li; Yen-Che Liao; Wen-Yen Chang; Chau-Huei Chen (Pure and Applied Geophysics, 2021)

High-order conservative and oscillation-suppressing transport on irregular hexagonal grids - Han Jiao; Xindong Peng; Yuzhang Che; Jun Chang (Meteorology and Atmospheric Physics, 2021)

First report of leaf blight on Cattleya × hybrid caused by Neoscytalidium dimidiatum in Taiwan - Che-Wei Chang; Chi-Yu Chen; Chih-Li Wang; Wen-Hsin Chung (Journal of Plant Pathology, 2020)

Real-time error correction of two-dimensional flood-inundation simulations during rainstorm events - Shiang-Jen Wu; Che-Hao Chang; Chih-Tsung Hsu (Stochastic Environmental Research and Risk Assessment, 2020)

The High-Frequency Decay Parameter (Kappa) in Taiwan - Shun-Chiang Chang; Kuo-Liang Wen; Ming-Wey Huang; Chun-Hsiang Kuo; Che-Min Lin; Chun-Te Chen; Jyun-Yan Huang (Pure and Applied Geophysics, 2019)

α -Pyrone derivatives with cyto-protective activity from two Takla Makan desert soil derived actinomycete Nocardiopsis strains recovered in seawater based medium - Tingting Zhao; Yimin Chang; Tianjiao Zhu; Jing Li; Qianqun Gu; Dehai Li; Qian Che; Guojian Zhang (Natural Product Research, 2019)

Characterization and adsorption capacity of potassium permanganate used to modify activated carbon filter media for indoor formaldehyde removal - Shih-Cheng Hu; Ying-Chen Chen; Xin-Zhi Lin; Angus Shiue; Po-Hua Huang; Yen-Che Chen; Shu-Mei Chang; Chao-Heng Tseng; Bin Zhou (Environmental Science and Pollution Research, 2018)

Studies on the Development of Small Abalone ( Haliotis diversicolor supertexta ) Essence and its Antioxidative Properties - Yu-Wei Chang; Chun-Che Lin; Wen-Chieh Sung (Journal of Aquatic Food Product Technology, 2018)

First report of cucumber mosaic virus infecting Arachis hypogaea in Jiangxi Province in China - Feng Zhu; Yan Ping Che; Yang Kai Zhou; Shi Chang Cheng; Zheng Liu; Zhao Lin Ji (Journal of Plant Pathology, 2018)

A case study of flood risk transfer effect caused by land development in flood-prone lowlands - Song-Yue Yang; Ming-Hsiu Chan; Che-Hao Chang; Chih-Tsung Hsu (Natural Hazards, 2018)

Assessing typhoon damages to Taiwan in the recent decade: return period analysis and loss prediction - Chia-Jeng Chen; Tsung-Yu Lee; Che-Min Chang; Jun-Yi Lee (Natural Hazards, 2018)

Neonatal Dexamethasone Treatment Exacerbates Hypoxia/Ischemia-Induced White Matter Injury - Chia -Yu Yeh; Che-Ming Yeh; Ting-Hsuan Yu; Kan-Hsun Chang; Chiung-Chun Huang; Kuei-Sen Hsu (Molecular Neurobiology, 2017)

Evaluating the contribution of multi-model combination to streamflow hindcasting by empirical and conceptual models - Yen-Ming Chiang; Ruo-Nan Hao; Hao-Che Ho; Tsang-Jung Chang; Yue-Ping Xu (Hydrological Sciences Journal, 2017)

Determining an Optimal Action Portfolio for Water Resource Management by Using Stochastic Programming - Chih-Chao Ho; Chen-Che Pan; Liang-Cheng Chang (Water Resources Management, 2017)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

Effects of Porphyromonas gingivalis on Titanium Surface by Different Clinical Treatment - Nominzul Batsukh; Sheng Wei Feng; Wei Fang Lee; Sy-Jye Leu; Pei-Yo Tsai; Kuo-Ning Ho; Che Tong Lin; Ching-Hua Su; Wei-Jen Chang (Journal of Medical and Biological Engineering, 2017)

Disentangling the effects of isolation-by-distance and isolation-by-environment on genetic differentiation among Rhododendron lineages in the subgenus Tsutsusi - Chun-Lin Huang; Jui-Hung Chen; Chung-Te Chang; Jeng-Der Chung; Pei-Chun Liao; Jenn-Che Wang; Shih-Ying Hwang (Tree Genetics & Genomes, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Erratum to: Nitrospirillum irinus sp. nov., a diazotrophic bacterium isolated from the rhizosphere soil of Iris and emended description of the genus Nitrospirillum - Eu Jin Chung; Tae Soon Park; Kyung Hyun Kim; Che Ok Jeon; Hae-In Lee; Woo-Suk Chang; Zubair Aslam; Young Ryun Chung (Antonie van Leeuwenhoek, 2015)

Translational Intracerebral Hemorrhage: a Need for Transparent Descriptions of Fresh Tissue Sampling and Preclinical Model Quality - Che-Feng Chang; Li Cai; Jian Wang (Translational Stroke Research, 2015)

Real-time correction of water stage forecast using combination of forecasted errors by time series models and Kalman filter method - Jhih-Cyuan Shen; Che-Hao Chang; Shiang-Jen Wu; Chih-Tsung Hsu; Ho-Cheng Lien (Stochastic Environmental Research and Risk Assessment, 2015)

Nitrospirillum irinus sp. nov., a diazotrophic bacterium isolated from the rhizosphere soil of Iris and emended description of the genus Nitrospirillum - Eu Jin Chung; Tae Soon Park; Kyung Hyun Kim; Che Ok Jeon; Hae-In Lee; Woo-Suk Chang; Zubair Aslam; Young Ryun Chung (Antonie van Leeuwenhoek, 2015)

Chronic hepatitis C virus infection triggers spontaneous differential expression of biosignatures associated with T cell exhaustion and apoptosis signaling in peripheral blood mononucleocytes - Muttiah Barathan; Kaliappan Gopal; Rosmawati Mohamed; Rada Ellegård; Alireza Saeidi; Jamuna Vadivelu; Abdul W. Ansari; Hussin A. Rothan; M. Ravishankar Ram; Keivan Zandi; Li Y. Chang; Ramachandran Vignesh; et al. (Apoptosis, 2015)

Therapeutic Efficacy of Neuro AiD™ (MLC 601), a Traditional Chinese Medicine, in Experimental Traumatic Brain Injury - Ming-Che Tsai; Ching-Ping Chang; Syue-Wei Peng; Kai-Sheng Jhuang; Yi-Hsien Fang; Mao-Tsun Lin; Thomas Chang-Yao Tsao (Journal of Neuroimmune Pharmacology, 2015)

Elucidation of anti-Vibrio factors associated with green alga Picochlorum sp. strain S1b - Jung-Che Kuo; Yu-Han Chang; Tsung-Yuan Chen; Yi-Min Chen (Journal of Applied Phycology, 2015)

Preparation and application of collagen scaffold-encapsulated silver nanoparticles and bone morphogenetic protein 2 for enhancing the repair of infected bone - Chang-ying Sun; Yan-jun Che; Shi-jin Lu (Biotechnology Letters, 2015)

Modeling the effect of uncertainties in rainfall characteristics on flash flood warning based on rainfall thresholds - Shiang-Jen Wu; Chih-Tsung Hsu; Ho-Cheng Lien; Che-Hao Chang (Natural Hazards, 2015)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Removal of Trihalomethanes and Haloacetic Acids from Treated Drinking Water by Biological Activated Carbon Filter - Jie-Chung Lou; Che-Jung Chang; Wei-Hsiang Chen; Wei-Bin Tseng; Jia-Yun Han (Water, Air, & Soil Pollution, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Benzodiazepine therapy in psychiatric outpatients is associated with deliberate self-poisoning events at emergency departments—a population-based nested case–control study - Hsin-I Shih; Ming-Chia Lin; Che-Chen Lin; Hsiang-Chin Hsu; Hsin-Ling Lee; Chih-Hsien Chi; Fung-Chang Sung; Yen-Jung Chang; Chia-Hung Kao (Psychopharmacology, 2013)

Cloning, expression and characterization of squalene synthase from Inonotus obliquus - Fangliang Zheng; Nan Liu; Yuchen Che; Li Zhang; Lijie Shao; Junfeng Zhu; Jian Zhao; Haixin Ai; Alan K. Chang; Hongsheng Liu (Genes & Genomics, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Reversine, a 2,6-disubstituted Purine, as an Anti-cancer Agent in Differentiated and Undifferentiated Thyroid Cancer Cells - Shih-Che Hua; Tien-Chun Chang; Hau-Ren Chen; Chieh-Hsiang Lu; Yi-Wen Liu; Shu-Hsin Chen; Hui-I Yu; Yi-Ping Chang; Ying-Ray Lee (Pharmaceutical Research, 2012)

Real-time correction of water stage forecast during rainstorm events using combination of forecast errors - Shiang-Jen Wu; Ho-Cheng Lien; Che-Hao Chang; Jhih-Cyuan Shen (Stochastic Environmental Research and Risk Assessment, 2012)

Reactive oxygen species-mediated PKC and integrin signaling promotes tumor progression of human hepatoma HepG2 - Chi-Tan Hu; Jia-Ru Wu; Chuan-Chu Cheng; Sindy Wang; Hsiao-Ting Wang; Ming-Che Lee; Ling-Jung Wang; Siou-Mei Pan; Tsu-Yao Chang; Wen-Sheng Wu (Clinical & Experimental Metastasis, 2011)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

A critical exploration of blood and environmental chromium concentration among oral cancer patients in an oral cancer prevalent area of Taiwan - Chi-Ting Chiang; Tsun-Kuo Chang; Yaw-Huei Hwang; Che-Chun Su; Kuo-Yang Tsai; Tzu-Hsuen Yuan; Ie-Bin Lian (Environmental Geochemistry and Health, 2011)

Effect of 1-methylcyclopropene on postharvest physiological changes of ‘Zaohong’ plum - Juan Kan; Jing Che; Hai Yan Xie; Chang Hai Jin (Acta Physiologiae Plantarum, 2011)

Modeling risk analysis for forecasting peak discharge during flooding prevention and warning operation - Shiang-Jen Wu; Ho-Cheng Lien; Che-Hao Chang (Stochastic Environmental Research and Risk Assessment, 2010)

Static magnetic field exposure promotes differentiation of osteoblastic cells grown on the surface of a poly-l-lactide substrate - Sheng-Wei Feng; Yi-June Lo; Wei-Jen Chang; Che-Tong Lin; Sheng-Yang Lee; Yoshimitsu Abiko; Haw-Ming Huang (Medical & Biological Engineering & Computing, 2010)

Identification and characterization of a mechanical transmissible begomovirus causing leaf curl on oriental melon - Ho-Hsiung Chang; Hsin-Mei Ku; Wen-Shi Tsai; Rui-Che Chien; Fuh-Jyh Jan (European Journal of Plant Pathology, 2010)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Reticulate hybridization of Alpinia (Zingiberaceae) in Taiwan - Shu-Chuan Liu; Chang-Tze Lu; Jenn-Che Wang (Journal of Plant Research, 2009)

Typing keystroke duration changed after submaximal isometric finger exercises - Che-Hsu (Joe) Chang; Peter W. Johnson; Jeffrey N. Katz; Ellen A. Eisen; Jack T. Dennerlein (European Journal of Applied Physiology, 2009)

Baicalein attenuates intimal hyperplasia after rat carotid balloon injury through arresting cell-cycle progression and inhibiting ERK, Akt, and NF-κB activity in vascular smooth-muscle cells - Chieh-Yu Peng; Shiow-Lin Pan; Ying-Wen Huang; Jih-Hwa Guh; Ya-Ling Chang; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Mana-Hox displays anticancer activity against prostate cancer cells through tubulin depolymerization and DNA damage stress - Che-Jen Hsiao; Yunn-Fang Ho; John T.-A. Hsu; Wei-Ling Chang; Yi-Cheng Chen; Ya-Ching Shen; Ping-Chiang Lyu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

A study of NO trafficking from dinitrosyl–iron complexes to the recombinant E. coli transcriptional factor SoxR - Feng-Chun Lo; Chang-Li Chen; Chien-Ming Lee; Ming-Che Tsai; Tsai-Te Lu; Wen-Feng Liaw; Steve S.-F. Yu (JBIC Journal of Biological Inorganic Chemistry, 2008)

Residual Stress Patterns Affect Cell Distributions on Injection-Molded Poly-l-Lactide Substrate - Sheng-Yang Lee; How Tseng; Keng-Liang Ou; Jen-Chang Yang; Kuo-Ning Ho; Che-Tong Lin; Haw-Ming Huang (Annals of Biomedical Engineering, 2008)

Static Magnetic Fields Promote Osteoblast-Like Cells Differentiation Via Increasing the Membrane Rigidity - Kang-Hsuan Chiu; Keng-Liang Ou; Sheng-Yang Lee; Che-Tong Lin; Wei-Jen Chang; Chang-Chih Chen; Haw-Ming Huang (Annals of Biomedical Engineering, 2007)

ORIGINAL ARTICLE: Phylogeography of the giant wood spider ( Nephila pilipes , Araneae) from Asian–Australian regions - Yong‐Chao Su; Yung‐Hau Chang; Sin‐Che Lee; I‐Min Tso (Journal of Biogeography, 2007)
Aim There are currently few population genetic studies on widely distributed SE Asian terrestrial organisms. We have studied the genetic diversification pattern of the giant wood spider, Nephila pilipes (Araneae: Tetragnathidae) to see whether fluctuations in rain forest extents generated by Quaternary climatic changes left signatures on populations of this agile terrestrial arthropod. Location The collecting localities were distributed in the following seven regions: (1) N Australia; (2) India (Calcutta, Karziranga and Sukna); (3) SE Asia (N Vietnam, Malaysia, Singapore and Bali); (4) SE China (Fujian, Guandong, Hong Kong and Hainan); (5) SW China (Guangxi and Yunnan); (6) E Asian islands (Ryukyu islands and Taiwan); and (7) the Philippine Islands. Methods A total of 374 specimens were collected from the East Asian continent and islands, SE Asia, India, and northern Australia. Mitochondrial cytochrome oxidase I gene partial sequences were used as the molecular marker to infer the phylogeographic diversification patterns. Results From the specimens collected, 67 haplotypes were identified, which could be grouped into five major clades. The dominant clade contained populations in regions ranging from Okinawa to Bali (spanning a distance of more than 4000 km), but their genetic variations were not structured and were not significantly associated with geographical distances. Three clades contained specimens collected from peripheral regions of the distribution range of N. pilipes , such as India, N Australia, and NE Asia. Members of the clade distributed in NE Asia were sympatric but those of the clades distributed in Australia and India were allopatric with those of the dominant clade. Main conclusions The results of this study indicate that, during Quaternary glacial periods, the rain forests in SE Asia might have been more or less continuous and thus generated an unstructured genetic diversification pattern of N. pilipes inhabiting this region. However, during such periods, populations in peripheral regions such as India, N Australia and NE Asia might have been isolated in refugia, thus accounting for the observed genetic divergence from populations in the SE Asian region.

Damage Survey of Water Supply Systems and Fragility Curve of PVC Water Pipelines in the Chi–Chi Taiwan Earthquake - Ban-Jwu Shih; Che-Hao Chang (Natural Hazards, 2006)

Natural Frequency Analysis of Periodontal Conditions in Human Anterior Teeth - Haw-Ming Huang; Sheng-Yang Lee; Ching-Ying Yeh; Mao-Sheng Wang; Wei-Jen Chang; Che-Tong Lin (Annals of Biomedical Engineering, 2001)

Increased expression of iNOS and c-fos via regulation of protein tyrosine phosphorylation and MEK1/ERK2 proteins in terminal bronchiole lesions in the lungs of rats exposed to cigarette smoke - Wen-Cheng Chang; Yuan-Chih Lee; Chuen-Lan Liu; Jeng-Dong Hsu; Hsue-Chun Wang; Chang-Che Chen; Chau-Jong Wang (Archives of Toxicology, 2001)

Comparison between `in vivo' and `in vitro' methods for evaluating tumor angiogenesis using cervical carcinoma as a model - Wen-Fang Cheng; Chien-Nan Lee; Chi-An Chen; Jan-Show Chu; Cheng-Che S. Kung; Chang-Yao Hsieh; Fon-Jou Hsieh (Angiogenesis, 1999)

Reproductive biology of the bigeye thresher shark,Alopias superciliosus (Lowe, 1839) (Chondrichthyes: Alopiidae), in the northwestern Pacific - Che-Tsung Chen; Kwang-Ming Liu; Yung-Chou Chang (Ichthyological Research, 1997)

The effect ofStaphylococcus epidermidis adherence to biomaterials—On antibiotic susceptibility, antibiotic release, and infection risk - Chung-Che Jeff Chang; Katharine Merritt (Annals of Biomedical Engineering, 1992)